Effectiveness of Mothers’ Training Based on Attachment Intervention on School Refusal and Social Competence of Children with Separation Anxiety Disorder - Motevally Joybari, Fatemeh; Babollah, Babollah; Abbasi, Ghodratollah (International Journal of Applied Behavioral Sciences, 2024)
Background and Objectives: One of the most common mental disorders in children is separation anxiety disorder, which can cause severe disorders in adulthood if not addressed. The present study examined the effectiveness of attachment-based training for mothers on school refusal and social competence of children with separation anxiety disorder. Materials and Method: The research method was semi-experimental with a pre-test-post-test design, one control group, and a three-month follow-up. The statistical population of this research was all the mothers of elementary school students suffering from separation anxiety disorder in District 1 of education in Sari, Iran, in the academic year 2022-2023. The research sample consisted of 30 mothers selected by purposeful sampling and randomly divided into experimental and control groups. Han, Hajinlian, et al.’s Separation Anxiety Questionnaire (2003), School Refusal Questionnaire by Carney and Silverman (1993), and Social Competence Questionnaire developed by the Behavior Problem Prevention Research Group (1995) were used for data collection. The experimental group received Korn-Carey, Dozier, and Ackerman’s (2004) and Cooper et al.’s (2005) intervention in eight 120–minute sessions; the control group did not receive any intervention. Before and after the training sessions, pre-tests and post-tests were taken from both groups. Applying SPSS 26, repeated–measures Analysis of Variance (ANOVA) was used for data analysis. Results: The results indicated a significant difference between the mean of school refusal and social competence in the pre-test-post-test and the pre-test-follow-up stages of the experimental group compared to the control group (P<0.05). Conclusion: The results indicate that attachment-based intervention training for mothers of children with separation anxiety disorder reduced school refusal and enhanced social competence in children with separation anxiety disorder.